El engagement y desempeño laboral de los trabajadores del centro de innovación productiva y transferencia tecnológica forestal de Maynas mayo 2022 - Benavente Estrada, Mayde Luz (2023)
Engagement in institutions is very important today because having engaged workers facilitates job performance and therefore the fulfillment of goals, because they are highly motivated, energized and happy. This thesis seeks to determine the relationship between the Engagement and work performance of the workers of the Center for Productive Innovation and Forest Technology Transfer of Maynas, May 2022, it is of a quantitative approach, correlational level, non-experimental and cross-sectional design. The research concludes that there is a very strong and significant positive relationship between Engagement and job performance of workers at the Maynas Center for Productive Innovation and Forest Technology Transfer, May 2022, demonstrated by Spearman's Rho Correlation Coefficient = 0.873** and p = 0.000; it also determines that there is a strong and significant positive relationship between Engagement and task performance, Engagement and Citizenship, and Engagement and Productivity; with Spearman's Rho Correlation Coefficients = 0.577** and p = 0.001; Spearman's Rho = 0.764** and p = 0.000 and Spearman's Rho Correlation Coefficient = 0.873** and p = 0.000, respectively